The complications of caesarean section among 100 cases - Sultana, Nargis; Khan , Sadia Jabeen; Sharifa , Begum Shaira; Akter , Tanvina; Sharmeen , Sabina (The Insight, 2021)
Objective: In this study our main goal is to evaluate the complications of Caesarean section among 100 cases. Method and materials: This prospective study was carried out at Department of Obstetrics and Gynaecology, Comilla Medical College Hospital, Comilla from January to June, 2003. Where total of 100 consecutive cases were selected for this study who underwent Caesarean section. Results: During the study, most of the women belonged to the age group 26-30 years (40%), followed by 21-25 (29 %), 31-35 (20%) and ≤20 years (11 %). Most of the common indication for caesarian section are fetal distress, 29% followed by obstructed labour were 22%, placenta praevia were 12%, 10% had history of previous caesarian section, 8% had transverse lie with hand prolapse. Maternal complications after caesarian section 5% had primary postpartum haemorrhage and wound infection followed by 1% had burst infection and 87% had no complication. 92% women suffered from no complication due to anaesthesia, the rest 6% experienced post spinal headache and only 2% experienced severe hypotension. Conclusion: From our study we can say that, all pregnant women should be screened by appropriately trained physicians, non-physician health workers with relevant expertise to identify risk factors and to provide ANC and care during labour. Also, strengthening maternal and child health programme by properly activating the health infrastructure e by trained manpower starting from village up to district level and above.